DIGITAL SERVICE DELIVERY TO RURAL POPULATIONS: CHALLENGES, MODELS, AND POLICY IMPLICATIONS FOR UZBEKISTAN - Sayfiddinov Vokhid Zokhidjonovich (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract The rapid advancement of digital technologies has created significant opportunities for improving service delivery in rural communities; however, a persistent digital divide between urban and rural populations remains a critical challenge in developing economies. This article examines the current state, barriers, delivery models, and policy implications of digital service provision in rural areas of Uzbekistan. Drawing on a systematic review of international literature, secondary statistical data, and comparative policy analysis, the study identifies the principal infrastructure, socioeconomic, and institutional obstacles that hinder rural digitalization. The paper evaluates four predominant implementation models — Common Service Centers, Mobile Digital Units, Agent Banking, and Cooperative Digitalization — and assesses their applicability within the Uzbek context. Findings indicate that targeted public-private partnerships, localized digital literacy programs, and subsidized connectivity are among the most effective policy instruments for bridging the rural-urban digital divide. The study concludes with evidence-based recommendations aligned with Uzbekistan’s Digital Uzbekistan 2030 strategy and the United Nations Sustainable Development Goals.